Paraneoplastic pemphigus: an association with fludarabine? - Gooptu, C; Littlewood, T; Frith, P; Lyon, C; Carmichael, A; Oliwiecki, S; MacWhannell, A; Amagai, M; Hashimoto, T; Dean, D; Allen, J; Wojnarowska, F (2001)
Paraneoplastic pemphigus is a relatively recently described immunobullous disease with characteristic features. We report three cases of paraneoplastic pemphigus in adult men with chronic lymphocytic leukaemia arising within a week of completion of treatment with fludarabine. In all cases, withdrawal of fludarabine and treatment of the blistering was associated with marked cutaneous improvement. Fludarabine, a synthetic nucleoside analogue, which has only been available in Britain since 1994, is known to be associated with autoimmune phenomena and may have been involved in the development of paraneoplastic pemphigus in these cases.